KEWENANGAN BALAI HARTA PENINGGLAN SEBAGAI KURATOR DALAM EKSEKUSI JAMINAN FIDUSIA DI BALAI HARTA PENINGGALAN MEDAN - MUHAMMAD ALI ADNAN (PREMISE LAW JURNAL, 2015)
Article 21 of Law No. 37/2004 stipulates that bankruptcy includes all debtors’ property at the time the ruling of bankruptcy is issued and anything obtained during the bankruptcy. The research was conducted to analyze the authority of Probate Court as the curator in the execution of fiduciary collateral in the Probate Court, Medan. The party claims to give the loan on the bankruptcy property and its claim for payment of the bankruptcy property. The result of the research shows that there is the authority of the Probate Court in organizing and settling bankruptcy property. The execution of fiduciary collateral in bankruptcy is conducted by the Probate Court, Medan. The party claims to give the loan on the bankruptcy property and its claim for payment of the bankruptcy property. The execution on fiduciary collateral is stipulated from Article 29 until Article 34 of Law No. 42/1999 on Fiduciary Collateral. It can be concluded that judicial problems must be solved so that the Probate Court as the curator of bankruptcy property can run maximally. Keywords: Authority, Probate Court, Execution of Fiduciary Collateral